2017
DOI: 10.1016/j.carbon.2016.10.065
|View full text |Cite
|
Sign up to set email alerts
|

Diameter dependence of the defect-induced Raman modes in functionalized carbon nanotubes

Abstract: Covalent functionalization of single-walled carbon nanotubes typically leads to an intensity increase of the defect-induced Raman mode (D mode). A large intensity ratio of the D and G modes (D/G ratio) is therefore often used as evidence for a successful functionalization. Here, we discuss the effect of the D-mode resonance on the D/G ratio and compare pristine and covalently functionalized nanotubes. By resonance Raman spectroscopy we study the evolution of the lineshape and frequencies of the D and 2D modes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Raman spectroscopy has shown itself to be a useful technique for monitoring nanotube modifications through observing changes in the nanotube's various bands that would indicate some change to the nanotube structure. Such observations have been used to support successful n-type modification in literature [13,14,65,[71][72][73].…”
Section: Chemical Dopingmentioning
confidence: 81%
“…Raman spectroscopy has shown itself to be a useful technique for monitoring nanotube modifications through observing changes in the nanotube's various bands that would indicate some change to the nanotube structure. Such observations have been used to support successful n-type modification in literature [13,14,65,[71][72][73].…”
Section: Chemical Dopingmentioning
confidence: 81%
“…Besides studying chirality and defects, the VDOS can also be used to calculate thermal conductivity. 48 Many properties of carbon nanotubes have been studied using Raman spectroscopy such as chirality and defects, 17,22,[49][50][51][52] but with this technique only certain Raman active phonon modes can be observed. 44,49,53 It is possible to study the full vibrational spectrum in experiments by inelastic neutron scat-tering, 49,54 or inelastic electron tunneling spectroscopy (IETS).…”
Section: Introductionmentioning
confidence: 99%
“…Such a large shift could stem from the simultaneously intense electronic and vibrational coupling at the interfaces of WS 2 and the SWCNTs . Furthermore, both the SWCNTs and hybrid composites exhibited a large peak intensity ( I G/D ) ratio, indicating a high quality of the SWCNTs with a small concentration of defects in the composites . From the inset of Figure b, it was found that apart from the characteristic peaks for WS 2 at 349 cm −1 (in plane E 1 2g ) and 417 cm −1 (out of plane A 1g ), there were also several new peaks observed in the low wavenumber range, which was similar with that of pure 1T‐WS 2 .…”
Section: Resultsmentioning
confidence: 61%